2023
DOI: 10.1186/s12889-023-15852-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the acceptability and feasibility of reactive drug administration for malaria elimination in a Plasmodium vivax predominant setting: a qualitative study in two provinces in Thailand

Abstract: Background Reactive case detection (RACD) or testing and treatment of close contacts of recent malaria cases, is commonly practiced in settings approaching malaria elimination, but standard diagnostics have limited sensitivity to detect low level infections. Reactive drug administration (RDA), or presumptive treatment without testing, is an alternative approach, but better understanding regarding community acceptability and operational feasibility are needed. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…pMDA and DOT heightened the morale and relationships between villagers and health care personnel in the study areas. Similarly, another study on reactive drug administration for P. vivax elimination in Thailand suggested that good acceptance of the program was related to education and sensitization campaigns on the purpose and rationale of the intervention [ 35 ]. Moreover, the WHO guidelines 2023 noted that a systematic review of 18 studies reported that the most common barrier to the acceptability of MDA for P. vivax was fear of adverse events, and some studies mentioned that sensitization on the benefits of MDA helped reduce concerns about adverse effects [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…pMDA and DOT heightened the morale and relationships between villagers and health care personnel in the study areas. Similarly, another study on reactive drug administration for P. vivax elimination in Thailand suggested that good acceptance of the program was related to education and sensitization campaigns on the purpose and rationale of the intervention [ 35 ]. Moreover, the WHO guidelines 2023 noted that a systematic review of 18 studies reported that the most common barrier to the acceptability of MDA for P. vivax was fear of adverse events, and some studies mentioned that sensitization on the benefits of MDA helped reduce concerns about adverse effects [ 32 ].…”
Section: Discussionmentioning
confidence: 99%